Influence of Continuous Flow Microwave Pre-Treatment on Anaerobic Digestion of Secondary Thickened Sludge for Sustainable Energy Recovery in Sewage Treatment Plant - Hephzibah D.; Kumaran P.; Saifuddin N.M. (Institute of Physics Publishing, 2023)
Anaerobic digestion; Biogas; Chemical oxygen demand; Energy conservation; Fatty acids; Irradiation; Microwave irradiation; Microwaves; River pollution; Secondary recovery; Sewage sludge; Sewage treatment plants; Volatile fatty acids; Biogas production; Biogas quantities; Continuous flows; Irradiation time; Microwave power levels; Pre-Treatment; Soluble chemical oxygen demands; Sustainable energy; Sludge digestion; anoxic conditions; biogas; chemical oxygen demand; concentration (composition); digestibility; experimental study; fatty acid; irradiation; pollutant removal; power generation; sewage; sewage treatment; sludge; solubility